ANALISIS KETERAMPILAN KOMUNIKASI PADA PEMBELAJARAN PERKENALAN DIRI BAHASA INGGRIS KELAS X SMK - Hayati Wasistyo Adi; Dinar Budi; Lina Murniasih; Nur Khirin; Muhimatul Iffadah; Yustinah Yustinah; Eny Winaryati (Journal of Lesson Study in Teacher Education, 2022)
Communication skills are one of the characteristics of 21st century learning. Students are required to have good communication skills to compete with the outside world. These skills can be started with self-introduction material which is the first material taught to class X students. The purpose of this research is to analyze students' communication skills in self-introduction material. With a lesson study approach that has a plan, do, see stage, students' communication skills are expected to improve. The subjects of this study were students of class X Islamic Banking at SMK Muhammadiyah 2 Boja. This type of research is qualitative. While the data obtained through observation, questionnaires, and interviews. Students were initially asked to write a self-introduction text with a small group. In these groups, students help each other and correct the results of their work. Not only self-introduction texts but also students' pronunciation or articulation when introduced orally. Students practice many times in the group. Then students come forward to get acquainted with their classmates. The discussion stage carried out by students was proven to increase their confidence when they came to the front of the class. Students can also compose self-introduction texts with correct vocabulary and grammar. Therefore, the implementation of lesson study to improve students' communication skills proved successful